Cytotoxicity of Carbon Nanotubes - Sementsov, Yu.; Aleksyeyeva, T.; Yermolenko, I.; Tin’kov, V.; Ieleiko, L.; Mikhailenko, V. (Наносистеми, наноматеріали, нанотехнології, 2012)
The industrial applications of carbon nanotubes (CNTs) for creating of new kinds of materials are limited because of their potential toxicity. There are many data concerning CNTs influences on the living body–from quite negative ones to the possibility of CNTs use in medicine. In a given work, the cell toxicity of CNTs on the example of healthy hepatocytes and Eirlich adenocarcinoma cells (EAC) is studied. As shown, the cells’ contact with CNTs suspension leads to the radicals’ release from cells. This radical release depends on both the time of cells’ contact with suspension and the CNTs concentration. As also shown, the influence of CNTs on EAC is essentially higher than that on healthy hepatocytes. Промислове використання вуглецевих нанорурок (ВНР) для виготовлення нових композиційних матеріялів обмежене їх потенційною токсичністю. В літературі є дані, які уможливлюють тлумачити вплив ВНР на живий організм від вкрай неґативного до можливого використання їх в медицині. Дану роботу присвячено вивченню токсичности ВНР на прикладі здорових клітин печінки (гепатоцитів) та клітин аденокарциноми Ерліха (ЕАК). Показано, що контакт клітин з суспензією ВНР призводить до викиду ними перекисних радикалів, а рівень викиду цих радикалів залежить від часу контакту і концентрації ВНР. Також було встановлено, що вплив ВНР на ЕАК є більш явним у порівнянні з гепатоцитами. Промышленное использование углеродных нанотрубок (УНТ) для создания новых композиционных материалов ограничено их потенциальной токсичностью. В литературе представлены данные, которые позволяют рассматривать влияние УНТ на живой организм как крайне негативное, так и позволяющее их использование в медицине. Данная работа посвящена изучению токсичности УНТ на примере здоровых клеток печени (гепатоцитов) и клеток аденокарциномы Эрлиха (ЭАК). Показано, что контакт клеток с суспензией УНТ приводит к выбросу клетками перекисных радикалов, уровень чего зависит от времени контакта и концентрации УНТ. Также показано, что влияние УНТ на ЭАК – более выраженное, чем на гепатоциты.